Relation between elevated uric acid and Lipid panel - AbuMustafa, Dr. Ayman M.; Tabash, Ahmad M.; Hejazi, Asmaa; Afana, Wesam M. (Jour Med Resh and Health Sci, 2019)
Background: Hyperuricemia is a very common metabolic disorder. Recently, A high uric acid noted that is associated with the risk of atherosclerotic cardiovascular diseases, inflammation and diabetes mellitus. The present study aimed to Relation between elevated uric acid and Lipid panel .Materials and Methods: A case-control study has been conducted on 70 hyperuricemia males with gout disease and 70vnormal uric acid males as control aged between 41-70 years. Lipid profile was measured, statistically analyzed and compared with control. Results: The results revealed significant differences between cases and control. The average levels of total cholesterol, triglycerides and LDL were significantly higher in cases compared to controls while HDL was significantly lower in cases compared to control. Pearson correlation showed that the ae positive significant correlation between uric acid and cholesterol (r=0.935, P<0.001), triglycerides (r=0.915, P<0.001) and LDL (r=0.914, P<0.001) while the results showed that there is a positive significant correlation between uric acid and HDL (r= -0. 834, P<0.001). Conclusions: Hyperuricemia should be treated because it has closed link with dyslipidemia disorder, therefore, both hyperuricemia and dyslipidemia will enhance the risk for cardiovascular disease. In the clinical filed, the more comprehensive strategic management to decrease hyperuricemia and dyslipidemia among adult males and deserves further investigation.